ANALISIS YURIDIS PELAKSANAAN LELANG EKSEKUSI TERHADAP PENYELESAIAN KREDIT MACET (STUDI PENELITIAN DI PT.BPR DANA NAGOY A) - Juey Yangta; Idham Idham; Titik Aminah (Ensiklopedia of Journal, 2023)
National Development Activities and Sustainable Economic Development for the achievement of general welfare in addition to requiring substantial funds, also requires legal rules to regulate and ensure the orderly implementation of economic activities both by the Government and the private sector. The rules referred to include how the rules so that the funds launched by granting credit by the banking sector to economic actors can be guaranteed return by the debtor. In principle, the new bank decides to provide credit, if the bank has obtained confidence about its customers The provision of credit by banks to customers is currently still very much emphasised on the importance of credit granting guarantees. What is meant by credit guarantee is needed by the bank to obtain certainty over the repayment of debts from customers after the period agreed in the credit agreement by making additional agreements or accesoir agreements. This research uses normative legal research and empirical law by using a normative approach method, namely research based on laws and regulations and an empirical approach to obtain primary data through research in the field. This research explains that how the legal arrangements and also explains how the implementation, obstacle factors and solutions in the implementation of the execution auction against the settlement of bad debts to realise legal certainty at PT BPR Dana Nagoya Batam City.The results of this study concluded that PT BPR Dana Nagoya ensures that before making efforts to resolve bad debts, namely giving the first to third warning letters to the debtor, if the warning letter is not responded to by the debtor, the debtor is invited to the office to be given a solution by means of resturcturisation, but if the solution does not find a solution, the bank executes the debtor's collateral object by making an application for an execution auction to the State Service Office and Auction (KPKNL).Keywords: Credit, Settlement, Auction.